2019
DOI: 10.1248/bpb.b18-00882
|View full text |Cite
|
Sign up to set email alerts
|

Brazilin Treatment Produces Antidepressant- and Anxiolytic-Like Effects in Mice

Abstract: Increasing evidence shows depression relevant to oxidative stress and inflammation. Anti-inflammatory strategies or antioxidants have led to the development of new antidepressants. Brazilin is a natural product from the Chinese traditional medicine Caesalpinia sappan L., exerting anti-inflammatory, antioxidant, anti-platelet concentration, and anti-cancer effects. While the antidepressant effect of brazilin is largely unknown. In present study, we investigated the effects of brazilin on H 2 O 2-induced oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…PC12 cells (from Prof. Di Wen, Hebei Medical University) were cultured in the high-glucose Dulbecco’s modified Eagle’s medium (DMEM) with 10% fetal bovine serum (FBS) at 37°C in a humidified incubator containing 5% of CO 2 . According to our previous study ( Wang et al, 2019 ), for the drug treatment, the cells were seeded onto a 96-well culture plate at 5 × 10 7 cells/well until full confluence (70–80%). After the treatment with CO-RM or saline for 1h, cells were incubated with H 2 O 2 (200 µΜ) for another 24 h in the culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PC12 cells (from Prof. Di Wen, Hebei Medical University) were cultured in the high-glucose Dulbecco’s modified Eagle’s medium (DMEM) with 10% fetal bovine serum (FBS) at 37°C in a humidified incubator containing 5% of CO 2 . According to our previous study ( Wang et al, 2019 ), for the drug treatment, the cells were seeded onto a 96-well culture plate at 5 × 10 7 cells/well until full confluence (70–80%). After the treatment with CO-RM or saline for 1h, cells were incubated with H 2 O 2 (200 µΜ) for another 24 h in the culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…The MTS assay was conducted according to the kit’s protocol ( Wang et al, 2019 ). Briefly, PC12 cells (5,000 cells/well) were seeded into 96-well microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
“…One of the core symptoms of MDD is anhedonia, which in the CUMS mice, was demonstrated by less sucrose consumption (14,19). Repeated administration of JYCF dramatically increased sucrose consumption and zone crossing times, which are the criteria for recognizing the (20). In the forced swim and tail suspension tests, immobility time was shortened compared with the CUMS group, which indicated that the depression had been alleviated (21).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that the majority of the beneficial pharmaceutical effects exerted by brazilin are concerned with its regulation on oxidative stress (14)(15)(16)(17)(18)(19). For example, Wang et al (14) suggested that brazilin exerted antidepressant-and anxiolytic-like effects in mice with chronically mild stress (CMS)-induced depression, probably through inhibiting oxidative stress. Moreover, Jayakumar et al (18) suggested that brazilin could suppress high glucose-induced vascular inflammatory processes partly via inhibiting ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilin, a homoisoflavonoid (C 16 H 14 O 5 ; chemical structure shown in Figure 1A), is a natural product of Caesalpinia sappan L. and it has been widely used as a traditional medicine for a long time in history (13). Brazilin has been reported to possess multiple pharmaceutical effects, including its efficacy in treating depressive and anxiety disorders (14), ameliorating oxidative stress-induced photoaging of skin (15), protecting auditory cells against t-butyl hydroperoxide (t-BHP)-induced cell death (16,17), suppressing high glucose-induced vascular inflammatory processes (18), extending lifespan in C. elegans (19) and so on. These effects are predominantly based on its powerful antioxidant activity, as evidenced by the fact that brazilin has been shown to inhibit antioxidant enzyme gene expression (16,17), lower the accumulation of intracellular ROS (18,19), and increase superoxide dismutase (SOD) activity (19).…”
Section: Introductionmentioning
confidence: 99%